Upper Washita River Experimental Watersheds: Meteorologic and Soil Climate Measurement Networks. Issue 4 (1st July 2014) - Starks, P. J.; Fiebrich, C. A.; Grimsley, D. L.; Garbrecht, J. D.; Steiner, J. L.; Guzman, J. A.; Moriasi, D. N.
Abstract : Hydrologic, watershed, water resources, and climate‐related research conducted by the USDA–ARS Grazinglands Research Laboratory (GRL) are rooted in events dating back to the 1930s. In 1960, the 2927‐km 2 Southern Great Plains Research Watershed (SGPRW) was established to study the effectiveness of USDA flood control and soil erosion prevention programs. The size of the SGPRW was scaled back in 1978, leaving only the 610‐km 2 Little Washita River Experimental Watershed (LWREW) to be used as an outdoor hydrologic research laboratory. Since 1978, the number of measurement sites and types of instruments used to collect meteorologic and soil climate data have changed on the LWREW. Moreover, a second research watershed, the 786‐km 2 Fort Cobb Reservoir Experimental Watershed (FCREW), was added in 2004 to the GRL's outdoor research laboratories to further study the effects of agricultural conservation practices on selected environmental endpoints. We describe the SGPREW, FCREW, and LWREW and the meteorologic measurement network (historic and present) deployed on them, provide descriptions of measurements, including information on accuracy and calibration, quality assurance measures (where known), and data archiving of the present network, give examples of data products and applications, and provide information for the public and research communities regarding access and availability of both the historic and recent data from these watersheds.